DEVELOPMENT AND CHARACTERIZATION OF FISH MEATBALLS PREPARED WITH MECHANICALLY SEPARATED MEAT OF AMAZON HYBRID SORUBIM COATED WITH SAFFLOWER FLOUR AT DIFFERENT GRANULOMETRIES - Fonseca, Gustavo Graciano; Cavenaghi-Altemio, Angela Dulce (Food and Feed Research, 2025)
The aim of this work was to develop a food alternative for consumers with celiac disease. Thus, fish meatballs were prepared from mechanically separated meat of Amazon hybrid sorubim (Pseudoplatystoma reticulatum x Leiarius marmoratus) and breaded with gluten-free safflower flour at two granulometries and characterized. Three treatments were evaluated: wheat flour (control) (T1), safflower at mesh 8 (T2), and safflower at mesh 14 (T3). Characterization was conducted through chemical, physical, microbiological, and sensory analyses. The moisture content of T1 (67.89%) was significantly higher (p<0.05) than T2 and T3. There was no significant difference (p>0.05) between treatments for protein content (10.85-11.60%). All treatments differed from each other in lipid and ash contents, the prior being higher for T2 (15.89%) and the former for T1 (1.53%). For crude fiber content, there was no difference (p>0.05) between T2 and T3, but statistically higher (p<0.05) than T1 (5.06%). Meatballs breaded with safflower flour (T2 and T3) presented significantly higher (p<0.05) pick-up values and shear force compared to those breaded with wheat flour (T1). These were related to the granulometry of the flour. The much statistically higher (p<0.05) redness (a*) observed for T2 and T3 was related to the presence of pigments bind to polysaccharides from flour. The panel mean scores (5.36–7.64) indicate sensory responses spanning indifference to moderate–high liking on the hedonic scale. Samples T2 and T3 presented acceptance indexes above 70% and T1 above 80%. The safflower-flour breading produced a darker color and an increased bitterness that reduced overall sensory appeal relative to the commercial wheat-flour coating, as reflected by lower sensory scores, acceptance index, and purchase-intent ratings. Hence, it is recommended to refine the formulations using alternative ingredients to address these sensory challenges.